Pemanfaatan Kotoran Domba Menjadi Pupuk Bokashi Terhadap Produktivitas Rumput Odot (Pennisetum purpureum cv. Mott) : The Effect of Sheep Manure on the Productivity of Odot Grass (Pennisetum purpureum cv. Mott) as Bokashi Fertilizer - Hidayat, Rahmat; Junaidi, Efri; Aswandi, Aswandi; Yusuf, Dwiky Andryawan; Fatkhrurrozi, Fatkhrurrozi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2026)
Background: Sheep farming as a sector that produces food as a source of animal protein, also produces a rarely used waste product, namely waste in the form of solid and liquid waste, providing a significant opportunity for use as an organic fertilizer, one of which is bokashi. Bokashi fertilizer is a fermented product of organic materials such as straw, husks, sawdust, animal manure, and more. Odot grass is a nutrient-rich grass that can grow in various locations. The need for green fodder can be met by planting green plants on fertile land. Planting odot grass using bokashi can increase soil productivity and increase the nutrient content of the grass. Purpose: This study aims to determine the nutrients (organic C, N, P, K),  contained in bokashi and to analyze the productivity of odot grass in the form of plant height, number of tillers and fresh dry weight. Methods: The research was structured using a Completely Randomized Design (CRD) with 3 treatments and 3 replications. The treatments given were P0: Bokasihi 0 gr + odot grass, P1: Bokashi 3840 g/2,56 m2 + Odot grass, P2: Bokashi 7680 g/2,56 m2 + Odot grass. Results: The test results on bokashi fertilizer still comply with the established SNI standards. The treatment of bokashi and odot grass had a significant effect (P<0.05) on plant height, number of tillers and fresh weight. Conclusion: Bokashi fertilizer contains high levels of macronutrients (N, P, K) and organic carbon,. A dose of 7680 g/2,56 m2 yielded the best results for odot grass productivity.